PERTUMBUHAN IKAN NILEM (Osteocliilus hasselti C.V) GINOGENESIS SAMPAI UMUR 30 HARI SERTA TINGKAT PERKEMBANGAN GONAD YANG TELAH DICAPAI [The Growth of Hard-Lipped Barlo (Osteocliilus hasselty C.V.) from Gynogenesis Until 30 Days and Gonad Development Stage Which Attained] - Kartika Dewi; Soeminto Soeminto (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2005)
Gynogenesis has been done in many kind of fishes that aims to produce only female homozygot population vastly. Gynogenesis can be used to improve genetic degree because the development of egg is solely controlled by the mother. If we use superior mothers, the characters can be inherited to their offspring. The purposes of this experiment were to know the rate of survival and length addition of gynogenesis nilem fish in laboratory until 30 days post hatching and to know the development stage of their gonad. This experiment produced two kind data. The first data were quantitative data such as survival rate and addition length rate of gynogenesis and control nilem fishes. Those data were analyzed with the t-test. The second data, qualitative data were collected by observing the texture and developmental stage of gonad. Then data were analyzed descriptively. The result showed that survival rate and addition length rate of gynogenesis and control nilem fishes of 30 days post hatching in the different density were different significantly with control fishes, but the rate of addition length of gynogenesis in nilem fishes were not different significantly with control. Whereas, microscopically gonad gynogenesis in nilem fish of 30 days post hatching was not different from control and undifferentiated. The appearance gonad was as sac that consisted of oval cells with a big size and with big nucleus too. Those big cells were suggested as primordial germ cells.